Expenditure patterns among low‐income families in China: Contributing factors to child development and risks of suicidal ideation. Issue 2 (23rd February 2022) - Xiao, Yunyu; Chow, Julian Chun‐Chung; Han, Keqing; Wang, Shencheng
Abstract: Low‐income families in urbsan China have been benefited from the Minimum Living Standard Guarantee Assistance ( dibao ) policy since 1999. However, little is known about how child‐specific family expenditure patterns impact child outcomes. Based on 2531 children aged 8–16 years from the National Survey of Social Policy Support System for Low‐Income Families in Urban and Rural China, this is the first study of its kind to (1) identify family expenditure patterns (food, apparel, housing, transportation, pocket money, after‐school education, and other educational resources) among low‐income families and (2) examine their relationship with child suicide risks and developmental outcomes (academic performance, mental health, and physical health) by sex and across the dibao and marginalized families (i.e., without dibao ). Latent profile analysis identified two patterns. Profile 1 (97.59%) showed low expenditure on children. Profile 2 (2.41%) prioritized expenditure in after‐school programs. Mixed‐effects logistic regression showed male children from marginalized families in Profile 1 are 11 times (95% confidence interval 1.10–109.52) more likely to think about suicide than female children from dibao families in Profile 2. Social policies and interventions promoting educational expenditure support and addressing the social determinants of health have the potential to reduce child suicide and improve child developmental outcomes among the urban poor.